Effects of electrode materials on solution-processed polyvinylidene fluoride-based piezoelectric nanogenerators: Do they matter?. (April 2022) - Ng, Yi Sheng; Yau, Zhi Yong; Ooi, Poh Choon; Auliya, Rahmat Zaki; Kurian, Thiresamary; Xie, Mengying; Tan, Sin Tee; Wong, Yew Hoong; Haniff, Muhammad Aniq Shazni Mohammad; Gan, Wee Chen; Tan, Chun Hui; Al-Bati, Sameer; et al.
Highlights: Examined the effects of electrode materials on solution-processed fabricated piezoelectric nanogenerators. Silver nanowires, indiun-tin-oxide, and poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate were used as electrodes. Various electrical characterizations were conducted to examine the effects of different electrode combinations. An equivalent circuit for a real capacitor is adopted to analyze further and identify the impedance manifestation. The data inciting that tuning the polyvinylidene fluoride impedance could improve the performance of the nanogenerators. Abstract: Numbers of energy harvesting studies have reported that using the appropriate electrode materials could enhance the electrical output performance of the energy harvesters. In this work, we fabricated polyvinylidene fluoride (PVDF)-based piezoelectric nanogenerators (PENGs) using the solution-process method. Different combinations of silver nanowires, indium-tin-oxide (ITO), and poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate were used as top and bottom electrodes to investigate the effect of electrode materials on the electrical output performance. The open-circuit voltage ( V OC ), short-circuit current ( I SC ), the charge generated, instantaneous areal power measured, and internal impedance were measured. The obtained data reveal no significant difference between the different electrode combinations, with a mean absolute deviation of 0.21 V, and 0.03 μA for V OC and I SC, respectively. Thereby, an equivalent circuit for a real capacitor is adopted to analyze further and identify the impedance manifestation attributed to the PVDF layer and electrode materials. Overall, the electrode materials have an insignificant impact on the electrical output performance of PVDF-based PENGs in this study. Nevertheless, the obtained data inciting that tuning the PVDF impedance by introducing the 2D MXene nanofillers approach could be useful information to improve the performance of solution-processed PVDF-based PENGs.